Estrategias de conservación ambiental y la comercialización de animales silvestres Belén Loreto.2024 - Martinez Manahuaco, Angie Fresia (2024)
This research work was conducted in the Belén Market sector and the lower area of Belén, with the objective of determining the relationship between the population's views on the commercialization of wild animals and the compliance with environmental management strategies implemented in the commercialization of wild animals in the Belén Market, District of Belén, in 2024. The research is quantitative in nature, prospective regarding data collection planning, relational in its research level, and non-experimental, cross-sectional in its design. The study involved the participation of 56 wild animal marketers working in the Belén market, who were present during the application of the data collection instrument. The survey technique was employed, and two questionnaires, each with 10 questions, were applied. These questionnaires had been previously validated and subjected to reliability testing. The obtained data were analyzed based on the research objectives and hypotheses, organized into a Basic Data Matrix (BDM), and subsequently processed, analyzed, and tabulated using SPSS statistical software, version 27. The main results indicated that the majority of wild animal marketers in Belén, Loreto, are men, which may suggest a male predominance in this economic activity. Additionally, the educational level of the respondents is relatively low, with a significant portion having only completed primary or secondary education. This situation suggests that many of them may lack adequate information regarding the conservation and sustainable management of wildlife, which could influence their commercial practices. It was found that the general perception of the commercialization of wild animals tends to be neutral, highlighting the need to improve environmental education, as greater awareness of the consequences of illegal wildlife trade could transform these perceptions and behaviors.